PERAN KINERJA PENGAWAS PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR BAGI PENINGKATAN KOMPETENSI PEDAGOGIK GURU PENDIDIKAN AGAMA ISLAM - Mohamad Muspawi (Pusat Penerbitan Universitas (P2U) Unisba, 2019)
AbstractThis study aims to determine the role of the performance of Islamic Education supervisors in improving the pedagogical competence of Islamic Religious Education teachers in Resort I State Elementary School Pelawan District. The research method used is a descriptive qualitative method, in which the researcher describes the research findings in a narrative and as-is. Data collection techniques used were observation, documentation, and interview techniques. To check the validity of the data, the author performs perseverance observation, triangulation, member check, audit trail. And to analyze the data the authors conduct data review and reduction, data unitization, data categorization, and data interpretation. The results showed that the role of the school supervisor's performance in improving the pedagogical competence of PAI teachers in Resort I State Elementary School Pelawan District was: 1. Carry out Teacher Subject Deliberation activities. 2. Provide positive input to PAI teachers. 3. Check the administrative completeness of the teacher. 4. Provide enlightenment on the development of the world of learning to teachers. Keywords: Supervisory; Performance; Teacher Competence. Abstrak Tujuan daripada kegiatan penelitian ini adalah untuk mengetahui peran kinerja pengawas dalam upaya peningkatan kompetensi pedagogik guru Pendidikan Agama Islam di Sekolah Dasar Negeri Resort I Kecamatan Pelawan. Menggunakan metode kualitatif deskriptif, yakni temuan penelitian diuraikan secara naratif dan apa adanya. Pengumpulan data menggunakan teknik obervasi, dokumentasi, dan wawancara. Pengecekan validitas data melalui ketekunan pengamatan, triangulasi, member check, audit trail. Penganalisisan data menggunakan penelaahan dan reduksi data, unitisasi data, kategorisasi data, dan interpretasi data. Hasil penelitian menunjukkan bahwa peran kinerja pengawas sekolah dalam meningkatkan kompetensi pedagogik guru Pendidikan Agma Islam (PAI) di Sekolah Dasar Negeri Resort I Kecamatan Pelawan adalah: 1. Melaksanakan kegiatan Musyawarah Guru Mata Pelajaran (MGMP). 2. Memberikan masukan yang positif kepada para guru Pendidikan Agma Islam (PAI). 3. Memeriksa kelengkapan administrasi guru. 4. Memberikan pencerahan mengenai perkembangan dunia pembelajaran kepada para guru. Kata Kunci: Kinerja; Pengawas; Kompetensi Guru.